Bioeroded coral species in Taklong Island Natriona; Marine Reserve, Guimaras. - Mariano, Marianne Isabelle J. (2019.)
Biological erosion (bioerosion) is the process of removing calcium carbonate (CaCO3) by organisms that bore or graze the coral reefs substrata. While there are many studies that looked at bioeroder and bioerosion rates in reefs, few have been undertaken in the Philippines nor looked at coral-bioeroder relationships or specificity. The study aimed to characterize the bioerosion activities in Taklong Island National Marine Reserve (TINMR), Nueva Valencia, Guimaras. Line transect method was used in determining live coral cover and the relative importance of bioeroded coral samples. ImageJ was used in estimating the bioeroded surface area of affected species. There were a total of 9 species of hard corals with indications of bioerosion. Among these two Porites species which were abundant in TINMR: Porites lobata and Porites sp2. Porites lobata was also the most vulnerable coral species to bioerosion. There were four bioeroders that were recorded: Ceraesignum maximum, Diadema setosum, Echinometra mathaei, and Spirobranchus sp. Overall, nineteen percent (19%) of the toal live coral surface area were considered to be bioeroded. This is relatively low bioerosion ratio however, continuous bioerosion activities can lead to a more serious threat to the coral community.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Bioeroded Corals -- Taklong Island Narional marine Reserve, Guimaras